PARTISIPASI MASYARAKAT DALAM MENDUKUNG KEBIJAKAN PENGELOLAAN SAMPAH DI PEKANBARU YANG BERDAMPAK PADA SUNGAI SIAK TAHUN 2019-2020 - Suharno, Rio Rahmat; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The production of waste every day is increasing along with the increasing number of products and people's consumption patterns. The thing that must be done to overcome the increase in the volume of waste is to reduce the volume of waste from the source through community empowerment.               The problems in community participation regarding waste management are what are the forms of regulations related to waste management in Pekanbaru City, what is the form of the mechanism for community participation in waste management and what factors affect community participation in waste management. Research on community participation-based waste management in Kelurahan Kampung Dalam Kota Pekanbaru aims to obtain an overview of the planning process and community-based household waste management, and propose community-based waste management proposals. This type of research is descriptive qualitative, namely research that intends to describe the phenomena that occur at the research location. Data collection techniques include interviews, observation and documentation.               Based on the results of the study, one form of community participation in efforts to improve the environment is by providing labor donations in the form of community service. In addition, they also hold a community meeting which is held once a month, which is attended by some residents at the RW level and all residents at the RT level. In this case, the RT level tends to take the form of direct participation, while the RW level takes the form of indirect participation. Residents do these activities without feeling forced at all. The form of community participation is influenced by the length of stay. Because the more people who are known, the stronger the psychological bond with their environment. Keywords: Community Participation, in Waste Management.